Tantrum Behavior of Children Aged 3-7 Years Viewed from Parental Parenting - Wulandari, Manda Oktafia; Susari, Hermawati Dwi; Anwar, Rosyida Nurul (Jurnal Pendidikan Anak, 2022)
A temper tantrum is an emotional disorder in children through excessive emotional outbursts such as shouting and crying and is characterized by aggressive body movements caused by parenting. Parenting patterns significantly impact the next child's growth and development. The purpose of the study was to determine how much influence parenting styles have on temper tantrum behavior in children aged 3-7 years. The research was conducted in Garon Village, Kawedanan District, Magetan Regency. The research method uses a descriptive quantitative approach. The number of samples in this study was 40 parents who have children aged 3-7 years. The sampling technique used was a simple random sampling technique. They are collecting data in the study using a questionnaire. The data analysis technique used is multiple linear regression analysis with SPSS. The results showed that authoritarian parenting significantly influences physical, aggressive tantrum behavior in children with a t-count = 1.906, greater than the t table = 1.689. Second, democratic parenting substantially influences children's physical, aggressive tantrum behavior with a t-value = 1.743, which is greater than the t-table value = 1.689. Third, permissive parenting substantially affects children's physical, aggressive tantrum behavior with at count = 3.067, which is greater than the t table = 1.689. Parenting applied by parents has a significant influence on children's behavior, so it is hoped that parents will pay more attention to the parenting used according to the child's development to avoid temper tantrums.